KAJI EKSPERIMENTAL PENINGKATAN SUB-COOLING KONDESER PADA KULKAS SATU PINTU MENGGUNAKAN AIR KONDENSAT - M. Fathan Sugih Bagja; Windy Hermawan Mitrakusuma; Triaji Pangripto Pramudantoro (KURVATEK, 2021)
Condensate water that collects in storage containers under the freezer cabin is often a problem in household refrigerators because it causes ice formation and puddles. In this final project, an experimental increase in sub-cooling in a single-door refrigerator is carried out by spraying condensate water on the kondenser outside the refrigerator every 2 minutes. It aims to utilize condensate water and improve system performance. After the measurement and data assessment process was carried out, the kondenser condition with spraying obtained chilling time for 38 minutes with the average data being stable from the 30th to the 36th minute resulting in an COPactual value of 3.2, COPcarnot 4.21, and an efficiency value. by 75.8%, while in kondenser conditions without spraying by condensate water, chilling time is obtained for 40 minutes with an average stable time from 32 to 38 minutes resulting in an COPactual value of 2.91, COPcarnot 3.97, and an efficiency value of 73.3 %. Then it can be concluded that the increase in sub-cooling using condensate water effectively utilizes condensate water and improves system performance.